Properties of Additive-Manufactured Open Porous Titanium Structures for Patient-Specific Load-Bearing Implants - Zumofen, Livia; Kopanska, Katarzyna S.; Bono, Epifania; Kirchheim, Andreas; De Haller, Emmanuel B.; Graf-Hausner, Ursula (Frontiers in Mechanical Engineering, 2022)
Additive manufacturing has been well established in many sectors, also in medical industry. For load bearing bone implants titanium and its alloys, such as Ti6Al4V are widely used, due to their high strength to weight ration and osseointegrative properties. However, bone resorption and loosening of implants is related to the significantly higher stiffness of dense Ti6Al4V, leading to stress shielding. With the ageing of population there is an increasing need for orthopaedic implants with high success rate and long implant life span. Besides that, the treatment of non‐healing segmental bone defects where the self‐repairing properties of bone tissue are not sufficient is still a challenge. In both fields of application patient specific titanium implants combined with functionally graded porosity designed according to locally expected loads unlock new possibilities. Many studies underline the huge potential of the new design freedom to generate open porous structures and more personalized implants with enhanced mechanical properties that also integrate well with surrounding tissues. Integration of functionally graded open porosity into implants allows for the implant to closer mimic the mechanical properties of human bone and its internal architecture. The results of this work represent the basis to develop complex porous titanium structures with various pore sizes and shapes to tailor structural mechanical properties and biological response. Therefore, 3D porous structures with various pore sizes and shapes were designed and manufactured in Ti6Al4V using laser powder bed fusion (PBF-LB/M). Based on these structures the correlation of pore size and shape with cell ingrowth, morphology, metabolic activity and early markers for bone formation (ALP activity) was investigated in static cell cultures using osteosarcoma cell line Saos‐2. Mechanical properties, such as the stiffness and compression strength were investigated with compression testing. The present study concludes that cell morphology, metabolic activity and ALP activity is widely independent of pore shape and size within the tested range of 400-700 µm pore size. Furthermore, the mechanical properties of the evaluated structures were in the range of cortical and trabecular bone. This opens the possibility to design mechanical properties with gradient porosity without decisively affecting biological response.